Attitude Of Teachers Towards Use Of English Language As A Medium Of Instruction In Secondary Schools In Republic Of Tanzania: A Pragmatic Perspective Of Community Secondary Schools In Arusha District - Etich E. J., Kirui Kipng; Ahmed, Osman; Lyimo, Naisujaki (Advances in Social Sciences Research Journal, 2017)
The purpose of this study was to establish the attitude of teachers towards the use of English as a language of instruction in Community Secondary Schools in Arusha District Tanzania. Despite the government initiatives, the achievement in Certificate of Secondary School Education Examination (CSEE) has been declining especially in the community secondary schools. The study attempted to answer the research question, what is the attitude of teachers towards the use of English as a language of instruction in Community Secondary Schools in Arusha District Tanzania? The study was conducted using descriptive survey in 26 Community Secondary Schools in Arusha Region Tanzania. Data was collected from 257 teachers selected randomly, 26 heads of schools and 1 District Education Officer purposely selected. Context, Input, Process and Product (CIPP) Model by Stufflebeam guided the study. Data collection was done through questionnaire and interviews. Descriptive statistics in terms of frequencies, mean scores, percentages and standard deviations were used to analyze quantitative data. Qualitative data was organized into themes as emerging from the field. The study established that limited competence in English as medium of instruction is a determinant in low academic achievement among students in Community Secondary Schools in Arusha District Tanzania. In order to increase students’ achievement, it is recommended that the Government of Tanzania should re-orientate its language policy in schools to enhance English competency among learners in secondary schools.